2003
DOI: 10.1677/joe.0.1770249
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic duodenal homeobox-1 and islet neogenesis-associated protein: a possible combined marker of activateable pancreatic cell precursors

Abstract: The aim of this work was to study the possible relationship between pancreatic duodenal homeobox-1 (Pdx-1) and islet neogenesis-associated protein (INGAP) during induced islet neogenesis. Pregnant hamsters were fed with (S) and without (C) sucrose, and glycemia, insulin secretion in vitro, and pancreas immunomorphometric parameters were measured in their 7-day-old offspring. S offspring had significantly lower glycemic levels than C animals. Insulin release in response to increasing glucose concentrations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 33 publications
3
24
0
2
Order By: Relevance
“…These changes modify the glucose set-point for insulin secretion, rendering -cells hypersensitive to glucose stimulation (Lenzen & Panten 1988, Epstein et al 1992, Lenzen 1992, Newgard 1992, Hosokawa et al 1995, Leahy 1996. We have previously reported that normal hamsters fed a SRD develop an insulin-resistance state that triggers functional and morphological changes in the endocrine pancreas (Massa et al 1997, Del Zotto et al 1999, Gagliardino et al 2003. Among these changes, we found an increased HK V max -without any significant changes in GK V max -and HK/GK activity-ratio.…”
Section: Discussionsupporting
confidence: 46%
“…These changes modify the glucose set-point for insulin secretion, rendering -cells hypersensitive to glucose stimulation (Lenzen & Panten 1988, Epstein et al 1992, Lenzen 1992, Newgard 1992, Hosokawa et al 1995, Leahy 1996. We have previously reported that normal hamsters fed a SRD develop an insulin-resistance state that triggers functional and morphological changes in the endocrine pancreas (Massa et al 1997, Del Zotto et al 1999, Gagliardino et al 2003. Among these changes, we found an increased HK V max -without any significant changes in GK V max -and HK/GK activity-ratio.…”
Section: Discussionsupporting
confidence: 46%
“…Previous studies have provided support for the hypothesis that INGAP is an important factor in an islet neogenesis cascade , Del Zotto et al 2000, Gagliardino et al 2003, Rosenberg et al 2004, Vinik et al 2004a. Despite these observations, the mechanisms by which INGAP acts on pancreatic cells to stimulate new islet growth is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…During the fetal and neonatal periods more new b-cells are formed by neogenesis (Bouwens et al 1994). Neogenesis is also observed in adult rodents after pancreatic injury such as streptozotocin injection (Fernandes et al 1997), partial pancreatectomy (Lee et al 1989), pancreatic duct ligation (Wang et al 1995, Xu et al 2008, cellophane wrapping of the pancreas head (Rosenberg & Vinik 1993), and in sucrose-induced insulin resistance (Del Zotto et al 1999, Gagliardino et al 2003.…”
Section: Introductionmentioning
confidence: 99%